(untitled) (The International Journal for Scientific Research, 2026)
The research aimed to identify the organizational silence and its relation to administrative development among administrative employees at Al-Balqa Applied University in Jordan, The descriptive correlational method was used, and the research population consisted of all administrative employees at Al-Balqa Applied University during the second semester of the year (2024/2025), who numbered (2524) administrative employees, and the research sample consisted of (398) administrative employees at Al-Balqa Applied University for the academic year (2024/2025), who were selected by the available random method. The researcher developed the questionnaire, which consisted of (72) items, after the validity and reliability of the of the research were verified, and it was distributed, and appropriate statistical treatments were conducted, and the results showed that the organizational silence among administrative employees at Al-Balqa Applied University reached a high level, the fields of organizational silence (social silence, acquiescent silence, defensive silence, opportunity silence) were arranged consecutively, and the field of "social silence", and the field of "acquiescent silence" reached a high level, also the field of "defensive silence", and the field of "opportunity silence" reached a moderate level, and the level of organizational silence among administrative employees at Al-Balqa Applied University reached a high. The results showed that the administrative development among administrative employees at Al-Balqa Applied University reached a moderate level, the fields of administrative development (legislation and regulations, work procedures and methods, training, and technology ) were arranged consecutively, and the field of legislation and regulations reached a high level, and the field of work procedures and methods, and the field of training, and the field of technology reached a moderate level, and the administrative development among administrative employees at Al-Balqa Applied University reached a moderate level, and the results of study showed that there were no statistically significant differences (α≤0.05) in the level of organizational silence among administrative employees at Al-Balqa Applied University, a as attributed to the study variables (gender, academic qualification, and years of service), and the results of study showed that there were no statistically significant differences (α≤0.05) in the level of the administrative development among administrative employees at Al-Balqa Applied University attributed to the study variables (gender, academic qualification, years of service), the results of study showed that there is a correlational relationship between level of organizational silence and level of administrative development among administrative employees at Al-Balqa Applied University. In light of the research results, the researchers recommended improving continuous training programs, promoting the level of technology used to administrative work by reconsider the technology used, developing strategies to interact with employees, enhancing motivation and appreciation for long years of serviced employees, organizing awareness campaigns about organizational silence and its effect, reviewing leadership structure and administrative transparency by fostering democratic leadership styles .